1998
DOI: 10.1093/humrep/13.5.1218
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional features of endometrial decidualization following long-term intrauterine levonorgestrel delivery

Abstract: Irregular bleeding remains a common reason for the discontinuation of progestin-only contraception. The levonorgestrel releasing intrauterine system (LNG-IUS) has profound morphological effects upon the endometrium. Specific features are gland atrophy and extensive decidual transformation of the stroma. Morphological changes in the endometrium may be associated with perturbation of mechanisms regulating normal endometrial function. This study describes endometrial stromal and glandular features prior to and up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(60 citation statements)
references
References 25 publications
4
54
0
2
Order By: Relevance
“…It releases 12 lg/24 h LNG into uterus cavity and has a life span of 3 years. In this study, the morphological changes of endometrium that is atrophic and inactive were similar to LNG-IUS-20 [1,2,10]. 12 lg of LNG per day proved to be effective in producing the suppression characterized by glandular atrophy and decidualization of stroma.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…It releases 12 lg/24 h LNG into uterus cavity and has a life span of 3 years. In this study, the morphological changes of endometrium that is atrophic and inactive were similar to LNG-IUS-20 [1,2,10]. 12 lg of LNG per day proved to be effective in producing the suppression characterized by glandular atrophy and decidualization of stroma.…”
Section: Discussionsupporting
confidence: 53%
“…It comprises a T-shaped plastic frame, with a cylinder of the synthetic progestogen levonorgestrel (52 mg), enclosed in a silastic sleeve allowing the controlled slow release of 20 lg daily of hormone into the uterine cavity. LNG from this system lead to obvious and profound effects on endometrial morphology and function atrophy of gland and changes in vascular morphology, an extensive decidualization of the stroma, increased stromal inflammatory reaction and dilation of capillaries , occasionally accompanied by thrombosis [1,2]. Moreover, the change of the uterine environment brings efficient contraception.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that levonorgestrel (LNG) administered either locally to the uterine cavity or systemically results in very significant morphological changes in the endometrium including gland atrophy, extensive decidual transformation of the stroma, and increased endometrial vasculature density. [1][2][3] With long-term LNG contraception, the vessels are enlarged, dilated, thinwalled, and fragile, suggesting they are the product of aberrant angiogenesis. 4,5 Indeed, a number of investigators have found a link between LTPOC-associated bleeding and aberrant expression of the angiogenic agent vascular endothelial growth factor (VEGF).…”
mentioning
confidence: 99%
“…Therapeutic progestogens that are highly androgenic result in endometrial atrophy. For example, marked endometrial atrophy is a feature of the endometrial response among women using a levonorgestrelreleasing intrauterine system (Critchley et al, 1998). As the suppressive effects of androgens on endometrial growth resemble the atrophic effects induced by anti-progestins, the possibility that the androgen receptor (AR) plays a role in anti-progestin action in human and non-human primate endometrium was evaluated using in situ hybridization, immunocytochemistry and ligand binding assays to assess changes in the endometrial AR during anti-progestin treatment .…”
Section: Is the Androgen Receptor Involved In The Endometrial Anti-prmentioning
confidence: 99%